Meningkatkan Daya Saing UMK: Mengungkap Peran Kecepatan Inovasi dan Penciptaan Pengetahuan - Darmawan, Baziedy Aditya; Firmansyah, Satya Laksana (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim : This study investigates the critical role of innovation speed and knowledge creation as antecedents of the competitiveness of MSEs in the culinary industry. Design/Method/Approach : Employing a multiple regression analysis, this study analyze data from 110 MSEs in Sleman and Yogyakarta. Research Finding : Our findings reveal that both, innovation speed and knowledge creation are significant drivers of MSEs’ competitiveness. Theoretical contribution/Originality : Building on the concept of knowledge-based barriers to entry, this study succeeded in demonstrating that rapid innovation fosters the creation of unique competence and market-based knowledge. Practitioner/Policy implication : These results offer valuable insights for MSEs, highlighting the importance of fostering a culture of continuous innovation and knowledge creation to achieve a sustainable competitive advantage. Research limitation : This study has limitations in the context of the sample and location, which were specifically conducted in Yogyakarta and Sleman, which may limit the generalizability of the result of this study.